El empleo de una base de datos para el estudio morfofonológico del ckunsa - Llanquiman Iturrieta, Eduardo Alejandro; Hasler Sandoval, Felipe Daniel; Torrico-Ávila, Elizabeth Mónica (Pontificia Universidad Católica del Perú, 2025)
This study focuses on the preservation and revitalization of Ckunza, the language of the Atacameño-Lickanantay Indigenous people. Based on the intersection between technology and language revitalization, it proposes the dissemination of a morphophonological linguistic database. The construction of the corpus was carried out in three phases: the compilation and analysis of a bibliographic list, the development of a lexicon containing Ckunza words extracted from that analysis and the morphophonological breakdown of each of those lexical forms. Potential lines of analysis include the frequency of graphemes and phonemes, the identification of syllabic patterns, the evaluation of morphemic consistency, and the detection of lexical borrowings. Possible outputs from these linguistic resources include digital applications, educational materials, and more effective translations. This study contributes to the promotion of linguistic and cultural diversity while strengthening the connection of Indigenous communities with their language using information and communication technologies. In particular, the digitalization of studies on Ckunza aims to advance linguistic justice for the Atacameño people.

Este estudio se enfoca en la preservación y revitalización del ckunsa, lengua de los indígenas del pueblo atacameño-lickanantay. Partiendo de la intersección entre la tecnología y la revitalización lingüística, se propone la difusión de una base de datos lingüística de tipo morfofonológica. El proceso de construcción del corpus se dividió en tres fases: la compilación y análisis de una lista bibliográfica, la elaboración de un lemario con palabras ckunsa extraídas de dicho análisis y el desglose morfofonológico de cada una de esas formas léxicas encontradas. Entre sus potenciales formas de análisis se encuentran: la frecuencia de grafemas y fonemas, la identificación de patrones silábicos, la evaluación de la coherencia de sus morfemas y la identificación de préstamos léxicos. Los posibles productos que resulten de estos recursos lingüísticos incluyen: aplicaciones digitales, materiales educativos y traducciones más eficaces. Este estudio aporta a la promoción de la diversidad lingüística y cultural, al tiempo que fortalece el vínculo de las comunidades indígenas con su lengua mediante el uso de tecnologías de la información y la comunicación. En particular, la digitalización de los estudios sobre el ckunsa busca avanzar hacia una mayor justicia lingüística para el pueblo atacameño.
Employing a Database for the Morpho-Phonological Study of Ckunsa
Keywords: Ckunsa; Information technologies; Morpho-phonological database; Cultural preservation; Linguistic revitalization; Ckunsa; Tecnologías de la información; Base de datos morfofonológica; Preservación cultural; Revitalización lingüística; https://purl.org/pe-repo/ocde/ford#5.04.03